Implementasi Konten Marketing Pada Akun Instagram @Kampunginggrisbandung Tahun 2024 - Alfaiz, Ramdhan; Mustikasari, Ati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Instagram is still one of the popular social media choices in Indonesia for marketing activities. This can be seen from the number of Instagram users in Indonesia which reaches hundreds of millions of people. Based on data from Napoleon Cat, there are 109.33 million Instagram users in Indonesia as of April 2023. English Village is a company operating in the education sector by offering various English language course programs such as Speaking Class, IELTS and TOEFL Preparation as well as bootcamp programs. English Village uses Instagram social media for marketing purposes, but in the midst of increasingly massive marketing competition for English language courses, the Instagram account used by the English Village for promotion is faced with a big challenge, because engagement from followers on Instagram is still relatively low and inconsistent at all times. type of content, even though the marketing division team always uploads various types of content on a scheduled basis. Based on the research conducted by the author, it can be concluded that planning, implementing marketing content that is right and interesting and consistent in carrying out regular evaluations will greatly influence customer engagement so that it can influence buying interest for customers and potential customers.